Pediatric Crohn disease: A case series from a tertiary care center - Kumar, Soma Santosh; Sindgikar, Seema Pavaman; Shenoy, Vijaya; Sinha, Smriti; Shankar, Raghu (Indian Journal of Child Health, 2019)
Crohn disease (CD) is an inflammatory bowel disease that causes transmural inflammation of the gastrointestinal tract. Growth failure is a major complication and can occur before gastrointestinal manifestations in children with CD. We present here four such cases where short stature and undernutrition constituted major symptomatology, along with enteric features. Median age of presentation was 13 years. Intermittent abdominal pain and growth failure were the predominant clinical manifestations. Features of imaging and colonoscopy were suggestive of CD. A poor response was noted to corticosteroids and azathioprine in three children. Clinical remission was not achieved as per abbreviated pediatric CD activity index score. One child succumbed to illness secondary to dilated cardiomyopathy. A good therapeutic response with significant weight gain was observed in two children after starting biologicals. Only one child responded to oral corticosteroids and mesalamine. Considering biologicals early in chronically active moderate to severe CD can help in altering the prognosis.